66 EFOMP: A global Player in the Education and Training of Medical Physics Experts. (December 2018) - Brambilla, M.
Abstract : Introduction: Promoting of education and training programmes is one of the columns of the mission of EFOMP. In this paper, I will briefly outline the initiatives taken from EFOMP in this field, namely: -The European School for medical Physics Experts (ESMPE) -The European Examination Board (EEB) - The participation of EFOMP in the EUTEMPE-RX network. ESMPE: EFOMP organized in 2013 the first module which was targeted towards Medical Physicists who would like to achieve Medical Physics Expert status in the Nuclear Medicine subspecialty. Since then, nine editions of the school have been completed with more than 400 participants coming from all European countries (see Fig. 1). The geographical distribution of participants demonstrate that this is perceived by participants as a European forum where state of the art information regarding technologies, methods and novelties in the field of medical Physics can be efficiently gathered and shared (see Fig. 2). A distinctive tract of the school is to provide subsidized fees for a certain number of participants coming from low income European countries. ESMPE at the second European Congress of Medical Physics – August 22, 2018, Copenhagen, Denmark The main congress (ECMP2018) will take place from 23 to 25 August 2018 in Copenhagen. Satellite meetings will be held in conjunction with the ECMP2018 on the 22 of August. Among them, ESMPE organized three satellite meetings. 1. Statistics in Medical Physics 2. Fundamentals of Nuclear Medicine Dosimetry 3. IMRT&VMAT planning in practice EEB: In many of EFOMP's NMOs a local examination board has not been established. Currently medical physicists from such countries face difficulties in providing the necessary qualification evidence when they seek employment in other EU Member States. The EEB has been established to facilitate the harmonization of medical physics standards throughout Europe, so facilitating the mobility of medical physicists The EEB main aims are to introduce 2 European Diplomas in Medical Physics: EDMP (European Diploma for Medical Physics) EACMPE (European Accreditation Certificate for Medical Physics Experts) The first round of EEB exams for Diagnostic and Interventional radiology took place in Prague July 6 and 7 2017. The second EEB round of examinations will took place August 21 and 22 2018 in all three fields of Medical Physics and will be held in conjunction with the 2 nd ECMP 2018 in Copenhagen. EUTEMPE-RX: Eutempe-RX is a Network of excellent teaching centers, which provides dedicated courses at EQF level8. The course contents are driven by the "Guidelines of the MPE project" with the support of a Scientific Advisory Board and they consist in balanced e-learning (40 hours workload) done through a Multicampus Educational and Training platform and face-to-face sessions (40 hours workload). The educational tools and methods includes: Creation of "groups of learners" and guided tasks prior to the face-to-face moments Online communication & feedback between teachers and learners Interactive self-assessment test Up-to-date multimedia material Solutions for practical training Interactive exercises Databases of Material